Deferasirox-induced urticarial vasculitis in a patient with myelodysplastic syndrome - Asude Kara Polat; Asli Akin Belli; Volkan Karakus; Yelda Dere (Sociedade Brasileira de Dermatologia, 2017)
Abstract Deferasirox is an iron chelator agent used in the treatment of diseases with iron overload, such as thalassemia and myelodysplastic syndrome. Although the majority of adverse reactions of deferasirox involve gastrointestinal symptoms and increase in serum creatinine and transaminases, skin rashes, such as maculopapular and urticarial eruptions, have also been reported. This study reports a case of myelodysplastic syndrome with urticarial vasculitis due to deferasirox therapy. Drug eruption was been confirmed by means of a challenge test, together with histopathological and clinical findings. To the best of our knowledge, we report the first case of deferasirox-induced urticarial vasculitis. Physicians should be aware of the possibility of urticarial vasculitis on deferasirox therapy and the fact that the discontinuation of the drug generally results in improvement.